El peso del integrismo en la Iglesia y el catolicismo español del siglo xx - Feliciano Montero (Mélanges de la Casa de Velázquez, 2014)
Fundamentalism, as the supreme expression of religious and political intolerance, is not an exclusively Spanish phenomenon. It should be viewed in the context of a long process of confrontation between the Catholic church and modernity and secularism, running from the anti-liberal intransigence of the Syllabus of 1864 to the Vatican II declaration on religious freedom. This article briefly outlines the course of that struggle, in the Spanish case, of fundamentalism against «accidentalism», highlighting particular points of tension: with accidentalism and the «unionist» proposals encouraged by the policy of Leo III in the 1880s and 1890s; with the more «populist» impulses from social Catholics, decried as «social modernists»; with the accidentalist and possibilist strategy of Tedeschini, Vidal i Barraquer and Ángel Herrera during the Second Republic; and lastly, with the conciliar «aggiornamento» and its impact in favour of a democratic regime.